Data mining and e-commerce : methods, applications, and challenges - Rastegari, Hamid; Md. Sap, Mohd. Noor (Penerbit UTM Press, 2008)
Electronic commerce processes and data mining tools have revolutionized many companies. Data that businesses collect about customers and their transactions are the greatest assets of that business. Data mining is a set of automated techniques used to extract buried or previously unknown pieces of information from large databases, using different criteria, which makes it possible to discover patterns and relationships. This paper discusses the important role of business based on data mining knowledge development to detection the relation of data mining and electronic commerce. And express some applications and challenges in this case.